Book Review: Regional geology and tectonics, volume 1: Principles of geologic analysis (2nd edition), by N. Scarselli, J. Adam, D.G. Roberts, A.W. Bally (Eds.), 2020. Elsevier B.V., Amsterdam, 894 pages. Paperback: price €183.75, ISBN 9780444641342. - Stawikowski, Wojciech (Geologos, 2021)
Book Review: Regional geology and tectonics, volume 1: Principles of geologic analysis (2nd edition), by N. Scarselli, J. Adam, D.G. Roberts, A.W. Bally (Eds.), 2020. Elsevier B.V., Amsterdam, 894 pages. Paperback: price €183.75, ISBN 9780444641342.